Lessons from modernism environmental design strategies in architecture, 1925-1970 - Bone, Kevin; Hillyer, Steven; Joh, Sunnie (The Monacelli Press, 2014)
This valuable reference for today's green building movement examines twentieth-century modern architecture, including buildings by Le Corbusier and Oscar Niemeyer, through the lens of sustainability